Pengembangan Media Pembelajaran Interaktif Matme Berbantuan Aplikasi Articulate Storyline Untuk Meningkatkan Penalaran Siswa Pada Materi Bilangan Bulat Kelas VII SMP Negeri Tonala Kabupaten Bolaang Mongondow Selatan Sulawesi Utara - Israwin Saman; Tedy Machmud; Franky Alfirst Oroh (Universitas PGRI Madiun, 2026)
Articulate Storyline is an ICT software that functions to create interactive audio-visual-based learning media. This application allows users to customize templates and characters as needed, making it easier for teachers to deliver material in an interesting and easy-to-understand way for students. Articulate Storyline is a useful tool for digital learning designers of all levels, from beginners to experts. In this study, the Articulate Storyline application was used to develop interactive learning media called